The effect of skill and incentives on employee performance at RSUD Dr. Soekardjo Tasikmalaya - Rida Qotrotul; Ilham Adnansyah; Nugi Mohammad Nugraha (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This research aims to determine the skills, incentives, and performance of employees at RSUD Dr. Soekardjo Tasikmalaya and to find out how much influence skills and incentives have on employee performance at Dr. Soekardjo Tasikmalaya for the period 2014-2018. The research used is the quantitative method. The sample used in this study were employees who worked at RSUD Dr. Soekardjo Tasikmalaya. Data processing was performed using Multiple Linear Regression, Correlation Analysis, and hypothesis testing. Based on the results of the study, it can be concluded that there is an influence between skills on the performance of the employees of Dr. Soekardjo Tasikmalaya and there is an influence between the provision of incentives on employee performance at Dr. Soekardjo Tasikmalaya. There is a simultaneous influence between skills and the provision of incentives on employee performance at Dr. Soekardjo Tasikmalaya